2015
DOI: 10.5551/jat.27425
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bezafibrate-induced Improvements in LDL Cholesterol in Dyslipidemic Patients with Diabetes

Abstract: Aim:Our previous "J-BENEFIT (Japan BEzafibrate cliNical EFfectIveness and Tolerability)" study demonstrated that bezafibrate improves blood lipid profiles and glucose control in dyslipidemic patients with diabetes. However, bezafibrate did not significantly improve low-density lipoprotein cholesterol (LDL-C), although some patients showed decreases while others showed increases in the LDL-C levels. Therefore, a subgroup analysis of the J-BENEFIT study was conducted to identify factors influencing the bezafibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Conversely, the majority of studies have demonstrated that SGLT-2 inhibitors reduce TG and increase HDL-C levels, which reduce atherogenic risk [2, 22]. TG-lowering agents, such as fibrates and omega-3 fatty acids, have a tendency to increase LDL-C [23, 24] probably because of reduced lipid transfer between TG-rich lipoprotein (TRL)-TG and LDL-C [25]. Therefore, it is not surprising that reduced levels of TG associated with SGLT-2 inhibitor use resulted in suppressed generation of cholesterol-poor LDL particles.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the majority of studies have demonstrated that SGLT-2 inhibitors reduce TG and increase HDL-C levels, which reduce atherogenic risk [2, 22]. TG-lowering agents, such as fibrates and omega-3 fatty acids, have a tendency to increase LDL-C [23, 24] probably because of reduced lipid transfer between TG-rich lipoprotein (TRL)-TG and LDL-C [25]. Therefore, it is not surprising that reduced levels of TG associated with SGLT-2 inhibitor use resulted in suppressed generation of cholesterol-poor LDL particles.…”
Section: Discussionmentioning
confidence: 99%
“…In the FIRST study, add-on administration of fenofibric acid with atorvastatin increased LDL-C by approximately 8% at 13 weeks and approximately 12% at 26 weeks, and a difference from that in the placebo group was also observed [23]. In the J-BENEFIT study, bezafibrate elevated LDL-C particularly in subgroups with lowbaseline LDL-C and high-baseline TG [24]. In the present studies, the percent change in LDL-C was positively correlated with baseline TG and inversely correlated with baseline LDL-C (data not shown), similar to the previous study [19].…”
Section: Discussionmentioning
confidence: 98%
“…In the former group, TGs and sd-LDL were also higher than those in the latter group, but there was no difference in non-HDL-C between the two groups (4.9 [4.0-5.4] mmol/L vs. 4.8 [4.5-5.2] mmol/L) [9]. Alternatively, the increase in TGs and decrease in LDL-C (calculated using Friedewald's formula) could have been synchronized [13,32], and the change in non-HDL-C might have been offset. The non-HDL-C measurement formula evaluates the cholesterol levels of TGs and LDL, which are rich in apoB.…”
Section: Discussionmentioning
confidence: 86%